Marketing Mixture Analysis On Product Sales Increase - Ade Perdana Siregar; Teguh Setiawan Wibowo; Pandu Adi Cakranegara; Uli Wildan Nuryanto; Muhammad Iqbal Fajri (Enrichment : Journal of Management, 2022)
This study aimed to analyze the effect of the marketing mix strategy consisting of product, price, place, and promotion on increasing sales volume of Reverse Osmosis Health Drinking Water. The research design used in this study used quantitative associative methods. Based on the results of data analysis that has been carried out on the first hypothesis (H1), which states that the product has a positive and significant effect on increasing sales, the value of t count > t table is 14,563 > 1,661, testing the second hypothesis (H2) which states that price has a positive effect and significantly to the increase in sales, the value of t count > t table is 12,293 > 1,661, testing the third hypothesis (H3) which states that place has a positive and significant effect on increasing sales, the value of t count > t table is 10,378 > 1,661 and on hypothesis testing fourth (H4) which states that promotion has a positive and significant effect on increasing sales, the value of t count > t table is 21,285 > 1,661 which means that product, price, place, and promotion have a positive and significant impact on increasing sales volume of Reverse Osmosis Health Drinking Water products, The R-square value obtained is 0.944, which states that the product, price, place, and promotion variables affect the sales volume of Reverse Osmosis Health Drinking Water products by 94.40%, and other variables influence the remaining 5.60%.